Influência do tamanho e da forma da semente de milho sobre o desenvolvimento da planta e a produtividade de grãos - Vazquez, Gisele Herbst [UNESP]; Arf, Orivaldo [UNESP]; Sargi, Bruno Antonio; Okamoto Pessoa, Allan Cesar (Universidade Federal de Uberlândia (UFU), 2012)
Due to the small and the round seeds represent a rather high proportion of an ear, this experiment viewed to study the effects of those factors on seed germinative performance in the field as well as on the plant traits related to grain yield. Six treatment combinations replicated five times were sown in Votuporanga/SP on 08/22/2008. Flat shaped (C) and round shaped (R) seeds were made to go through flat round and oblong hole screens which resulted in the following treatments: 1. C1: seeds remaining on the top of a 23/64 '' round hole screen, 2. C2G: 21/64 '', 3. C3M: 17/64 '' or 16/64 '', 4. R2GM: medium length seeds remaining on the top of 13 x 3/4 '' oblong hole screen, 5. R3M: medium length seeds remaining on a 12 x 3/4 '' (from 1 to 2 mm bigger than R3), and 6. R3: 12 x 3/4 ''. The soil of the experimental area was submitted to a no-till cultivation system and the rows were set 0.6 m apart from one another. Fifteen days after emergence (DAE), the plants were thinned to a population of 66,000 plants/ha. Harvest took place 115 DAE and the mean yield was of 12,498 kg ha(-1). Based on the results it was concluded that only the initial growth of the plants is significantly affected by seed size. Plant traits such as plant height, ear insertion height, culm diameter, number of grains per year, grain weight and size as well as grain yield evaluated 40 or more DAE are not significantly affected by seed size or seed shape.

O objetivo deste trabalho foi verificar a influência do tamanho e da forma da semente de milho empregada no momento da semeadura sobre o desenvolvimento da planta e a produtividade de grãos. O experimento foi instalado no dia 22/12/2008 em Votuporanga, SP, com seis tratamentos e cinco repetições. Lotes comerciais de sementes de milho híbrido simples DKB 390YG classificados com os seguintes tamanhos (peneiras - P) e formas (achatadas – C ou redondas – R) foram avaliados: 1. C1 (semente retida em P23/64”), 2. C2G (P21/64”), 3. C3M (P17/64” ou 16/64” de comprimento médio); 4. R2GM (P13 x ¾” médio), 5. R3M (P12 x ¾’’ de comprimento 1 a 2 mm maior que a R3) e 6. R3 (P12 x ¾’’). A área foi semeada em sistema plantio direto em um espaçamento de 0,6 m entrelinha, e aos 15 dias após a emergência foi realizado um desbaste para a obtenção de 66.000 plantas ha-1. A colheita foi realizada aos 115 dias após a emergência atingindo produtividade média de grãos de 12498 kg ha-1. De acordo com os resultados obtidos pode-se concluir que alterações no tamanho de sementes de milho interferem apenas no desenvolvimento inicial das plantas. Após 40 dias da emergência, a altura da planta e da inserção da primeira espiga, o diâmetro do colmo, o número de grãos por espiga, o peso e o tamanho do grão colhido e a produtividade de grãos não sofrem interferência do tamanho e da forma da semente de milho empregada em semeadura normal de verão.
Corn seed size and shape influence on plant growth and grain yield
Keywords: Zea mays; Seed processing; Classification of seed; Screen